Reward-related brain activity and behavior are associated with peripheral ghrelin levels in obesity. (February 2020) - Bogdanov, Volodymyr B.; Bogdanova, Olena V.; Dexpert, Sandra; Delgado, Ines; Beyer, Helen; Aubert, Agnès; Dilharreguy, Bixente; Beau, Cédric; Forestier, Damien; Ledaguenel, Patrick; Magne, Eric; Aouizerate, Bruno; et al.
Highlights: Obese subjects exhibited reduced serum fasting levels of ghrelin when compared to non-obese control subjects. Activation in dorsolateral prefrontal cortices during non-food reward processing was greater in obese subjects. Significant associations were found between reduced ghrelin levels and slower post-reward choices. Reward-related hyperactivity in dorsolateral prefrontal cortices correlated with reduced ghrelin levels. Abstract: Background/objectives: While excessive food consumption represents a key factor in the development of obesity, the underlying mechanisms are still unclear. Ghrelin, a gut-brain hormone involved in the regulation of appetite, is impaired in obesity. In addition to its role in eating behavior, this hormone was shown to affect brain regions controlling reward, including the striatum and prefrontal cortex, and there is strong evidence of impaired reward processing in obesity. The present study investigated the possibility that disrupted reward-related brain activity in obesity relates to ghrelin deficiency. Subjects/methods: Fifteen severely obese subjects (BMI > 35 kg/m 2 ) and fifteen healthy non-obese control subjects (BMI < 30 kg/m 2 ) were recruited. A guessing-task paradigm, previously shown to activate the ventral striatum, was used to assess reward-related brain neural activity by functional magnetic resonance imaging (fMRI). Fasting blood samples were collected for the measurement of circulating ghrelin. Results: Significant activations in the ventral striatum, ventromedial prefrontal cortex and extrastriate visual cortex were elicited by the fMRI task in both obese and control subjects. In addition, greater reward-related activations were present in the dorsolateral prefrontal cortex, and precuneus/posterior cingulate of obese subjects compared to controls. Obese subjects exhibited longer choice times after repeated reward and lower circulating ghrelin levels than lean controls. Reduced ghrelin levels significantly predicted slower post-reward choices and reward-related hyperactivity in dorsolateral prefrontal cortices in obese subjects. Conclusion: This study provides evidence of association between circulating ghrelin and reward-related brain activity in obesity and encourages further exploration of the role of ghrelin system in altered eating behavior in obesity.